Paediatric Posttraumatic Cyst-Like Lesions: A Report of Two Cases and Review of the Literature - R. Jansen; F. van Rooijen; J. P. Toirkens; A. T. Besselaar; J. J. Tolk (Case Reports in Orthopedics)
Posttraumatic cyst-like lesions are a rare finding after greenstick fractures in children. These asymptomatic, cystic lesions become radiologically apparent 2-4 months after the initial trauma. Conventional radiographs typically show nonexpansile, well-circumscribed lesions in the cortex, proximal to the fracture site. It is important to recognize them as benign to prevent unnecessary concern and additional imaging or invasive diagnostic procedures. No treatment is indicated, as they eventually resolve spontaneously in 1 to 3 years. The two cases of posttraumatic cyst-like lesions after paediatric forearm fractures are presented.